2012
DOI: 10.1536/ihj.53.293
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Output Response to Exercise in Chronic Cardiac Failure Patients

Abstract: SummaryThe purpose of this study was to investigate the precise pattern of stroke volume (SV) response during exercise in patients with chronic heart failure (CHF) compared with age-matched controls. Fourteen patients with CHF and 7 controls performed symptom-limited bicycle exercise testing with respiratory gas exchange measurement. Patients were classified into group A (n = 7) with peak V ・ O 2 ≥18.0 mL/kg/minute and group B (n = 7) with peak V ・ O 2 < 18.0 mL/kg/ minute. SV and cardiac output (CO) were cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…Previous studies using non‐invasive estimates of cardiac haemodynamics showed strong associations between CO and VO 2 at peak exercise ( r = 0·81 Fukuda et al ., ; r = 0·72 Myers et al ., ) in heart failure patients. Differences in the strength of the correlations reported in previous investigations and what was found in the current study may be the result of the characteristics of the chronic disease population assessed.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies using non‐invasive estimates of cardiac haemodynamics showed strong associations between CO and VO 2 at peak exercise ( r = 0·81 Fukuda et al ., ; r = 0·72 Myers et al ., ) in heart failure patients. Differences in the strength of the correlations reported in previous investigations and what was found in the current study may be the result of the characteristics of the chronic disease population assessed.…”
Section: Discussionmentioning
confidence: 97%
“…Witte et al supported the concept that chronotropy is not a major factor in determining exercise capacity in patients with CHF [19], suggesting that HR limitation is unlikely to be the cause, but rather the consequence, of exercise intolerance in CHF patients [21]. Fukuda et al demonstrated that CHF patients with impaired exercise capacity had attenuated increments in cardiac output during exercise [22].…”
Section: Discussionmentioning
confidence: 98%
“…Evidence of cardiac rehabilitation has been shown in patients with heart disease. [10][11][12][13] However, there is little evidence of nutritional management in HF patients and the most appropriate nutritional assessment has not yet been established.…”
mentioning
confidence: 99%